Negotiating Health Amidst COVID-19 Lockdown in Low-income Communities in Aotearoa New Zealand. Issue 1 (2nd January 2021) - Elers, Christine; Jayan, Pooja; Elers, Phoebe; Dutta, Mohan J.
ABSTRACT: Aotearoa New Zealand's public health crisis communication approach amidst the COVID-19 pandemic effectively mobilized the nation into swift lockdown, significantly reducing community transmission. This communication approach has been applauded around the world. How did communities situated amongst the "margins of the margins" in Aotearoa New Zealand navigate through the existing structural barriers to health during the pandemic? In this study, we use a culture-centered analysis to foreground the structural context of disenfranchisement amidst the COVID-19 lockdown. Drawing on in-depth interviews with participants in a larger ethnographic project on poverty and health across three communities in Aotearoa New Zealand, we attend to the ways in which health is negotiated amidst the COVID-19 outbreak and lockdown response at the "margins of the margins." The narratives point out that health communication interventions to prevent COVID-19 in the context of Aotearoa New Zealand furthered the marginalization of communities at the margins, and community voices were largely erased from the enactment of interventions. With the extant structures failing to recognize these aspects of everyday struggles of health at the margins, the health and access challenges were further magnified during COVID-19. Our attention to communication situated in relationship to structures builds a register for health communication scholarship in the context of COVID-19 that is committed to disrupting the behaviorally based hegemonic health communication literature and transforming the unequal terrains of health experiences.